CONFIGURATION SELECTION METHOD WITH FUZZY DECISSION MAKING IN PREVENTION PORPOISING ON FLOATER N219 - Windha Umi Alifia (Journal of Marine-Earth Science and Technology, 2025)
Porpoising leads to hull damage an inconvenience for passengers and crew in ship operations, especially ships with high Fn. Porpoising is one type of ship and floatplane instability. The choice of ship and floater configuration can prevent the occurrence of porpoising instability. Configuration selection using fuzzy logic method with multiple attribute decision making for 8 variables with 6 configurations of deadrise angle β and LCG longitudinal centre of gravity of a ship. Determination of objective configuration scenario and objective function for optimum configuration selection. Region or domain clustering is performed for each variable in all six configurations. Membership value assessment is carried out by entering the input of the configurations. Membership value assessment is carried out by entering the input of the configuration variable into the membership function to obtain the membership value or degree of the six configurations. For each variable, plotting is also carried out to the region in the existing region division. Configuration selection gets 2 alternatives, namely by clustering the best configuration of deadrise angle of 20° and LCG value of 55% and the configuration of deadrise.